Pertunjukan Pantomim ”diskriminasi bagai gelap” oleh Kelompok Gerkatin Cabang Makassar Analisis Representasi Sosial Teman Tuli - B, Fajrin; Putri, Sulfiana Mansyur (CV. ITTC INDONESIA, 2024)
Staging Dark Discrimination represents the social life of deaf friends seen through the values of life practiced. The values practiced are: social values, religious values, and moral values. Through the Dark Discrimination show, it will be described in relation to the formulation of the problem: the dramatic structure of the Dark Discrimination show, as well as the deaf friends' social representations presented in the Dark Discrimination show. The process of elucidating the problems of the deaf friends' social lives is first described as a Dark Discrimination show. Next is Gustav Freytag's dramatic structural theory for dissecting the dramatic structure of the Dark Discrimination show. The theory used to analyze social representation is the theory of construction and cultural reproduction of Irwan Abdullah. This interpretive qualitative research method will use qualitative data obtained from the video documentation of the Dark Discrimination Show, while the data collection used is the study of documentation, literature, and interviews. The Dark Discrimination Show is a social representation of deaf friends, and the figures presented by deaf friends represent the image of the people in Makassar. The picture of the deaf friend's social life as outlined in Dark Discrimination through forms of representation from the social, economic and religious aspects that we can see from the values of their daily practices. Values that are practiced and expressed in the show are: Social values, religious values, and moral values. The values which are each illustrated through the figure of the Deaf in Dark Discrimination. Starting from the sensitivity of deaf friends to the community, triggering deaf friends in making the work of Dark Discrimination. The sensitivity of deaf friends is reflected in the dramatic structure of the Dark Discrimination show that practiced values are closely related to deaf friends' behavior.